FOREIGN DIRECT INVESTMENT AND CAPITAL FORMATION: POLICY IMPLICATIONS TOWARDS ACHIEVING PRO-POOR GROWTH IN NIGERIA - OLOWE, OLUKEMI OLUMUYIWA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2022)
This study examines the links between foreign direct investment (FDI) and capital formation in Nigeria within the period of 1981-2020. The estimation approaches used are augmented Dickey Fuller test for stationarity level of our data sets and the autoregressive distributed lag (ARDL) model for short- and long- run relationship between the FDI and capital formation. The unit root test result indicated that interest rate and inflation rate were stationary at levels while other variables - FDI, government expenditure, gross domestic product, exchange rate and capital formation were reported to be stationary at first difference. Using the autoregressive distributed lag model, it confirmed that there is a long-run relationship between FDI and capital formation in Nigeria. The results further show FDI has positive and significant impact on capital formation in Nigeria. Other factors that positively influenced capital formation are government expenditure, gross domestic product and interest rate. However, exchange rate and inflation rate have negative impact on private investment in Nigeria. The study suggests the need for government to continue attracting foreign investment as it stimulates the capital formation channel towards enhancing output growth that is capable of promoting poor. Also, the financial sector most especially the apex bank, should ensure proper mobilization of investible fund in the economy through high saving deposit rates and accessibility of such fund by private investors through low lending rate.